Improving French bean yield potential through induced mutagenesis using EMS and SA - Laskar, Rafiul Amin; Dowarah, Bhaskar; Tamang, Dilip; Das, Sangeeta; Borah, Protiva; Raina, Aamir (Frontiers in Horticulture, 2024)
French bean (Phaseolus vulgaris L.) holds global significance as one of the most consumed legumes, with commercial value surpassing that of all other legume crops combined. In India, the consumption of French beans has grown steadily, especially in the North Eastern region, driven by heightened consumer interest in its nutritional benefits. Considering these factors, we initiated an induced mutagenesis program to enhance the genetic diversity of locally grown French bean genotypes, traditionally cultivated for their superior adaptability. Seeds from the village seed stock were treated with varying doses of ethyl methane sulfonate (EMS) ranging from 0.1% to 0.4% and sodium azide (SA) from 0.1% to 0.4% to increase yield potential. Exposure to EMS and SA resulted in a non-specific and dosage-independent reduction in biophysiological characteristics in French bean mutants. Mutagenic doses, particularly at 0.4% SA treatment, significantly inhibited germination and fertility, leading to a decrease in chlorophyll (10.02 mg.g-1FW) and carotenoid (1.57 mg.g-1FW) levels-a sign of mutageninduced disruption in genes associated with chlorophyll and carotenoid synthesis. In the M2 generation, mutagenic treatments substantially improved yield and associated traits in the French bean cultivar, with the highest pod yield per plant recorded at 0.2% EMS treatment (79.50 gm). The character association study revealed strong correlations (ranging from 0.217 to 0.995) between pod yield and other agronomic traits, suggesting that selecting mutants based on these traits within treated populations, influenced by EMS and SA, has the potential to significantly increase crop yield. Notably, the 0.2% SA and 0.2% EMS M2 mutant populations exhibited the highest induced variability, making them ideal candidates for selecting higheryielding mutant lines for advancement into subsequent breeding generations. With significant increases in yield, we envisage releasing these mutant lines, sourced from seeds of a local cultivar, for widespread cultivation, effectively meeting the growing demand for French bean production.